The Influence Of Financial Ratio On Financial Distress In Transportation Sub-Sector Companies - Riza Cahaya Safitri; Rita Meiriyanti; Prianka Ratri Nastiti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to find out how financial ratios influence a company’s financial distress. These financial ratios consist of profitability, liquidity, leverage and activity ratios in transportation sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This research was conducted using a purposive sampling method. Data collection techniques use secondary data. Data was collected from transportation sector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022 using the Multiple Linear Regression method using SPSS 21. The financial distress variable was proxied using the Springate formula (S-score). The results of this research show that the variables profitability, liquidity, leverage and activity have a significant influence on financial distress.